C188-9, a specific inhibitor of STAT3 signaling, prevents thermal burn-induced skeletal muscle wasting in mice - Ono, Yuko; Saito, Masafumi; Sakamoto, Kazuho; Maejima, Yuko; Misaka, Shingen; Shimomura, Kenju; Nakanishi, Nobuto; Inoue, Shigeaki; Kotani, Joji (Frontiers in Pharmacology, 2022)
Burn injury is the leading cause of death and disability worldwide and places a tremendous economic burden on society. Systemic inflammatory responses induced by thermal burn injury can cause muscle wasting, a severe involuntary loss of skeletal muscle that adversely affects the survival and functional outcomes of these patients. Currently, no pharmacological interventions are available for the treatment of thermal burn-induced skeletal muscle wasting. Elevated levels of inflammatory cytokines, such as interleukin-6 (IL-6), are important hallmarks of severe burn injury. The levels of signal transducer and activator of transcription 3 (STAT3)—a downstream component of IL-6 inflammatory signaling—are elevated with muscle wasting in various pro-catabolic conditions, and STAT3 has been implicated in the regulation of skeletal muscle atrophy. Here, we tested the effects of the STAT3-specific signaling inhibitor C188-9 on thermal burn injury-induced skeletal muscle wasting in vivo and on C2C12 myotube atrophy in vitro after the administration of plasma from burn model mice. In mice, thermal burn injury severity dependently increased IL-6 in the plasma and tibialis anterior muscles and activated the STAT3 (increased ratio of phospho-STAT3/STAT3) and ubiquitin-proteasome proteolytic pathways (increased Atrogin-1/MAFbx and MuRF1). These effects resulted in skeletal muscle atrophy and reduced grip strength. In murine C2C12 myotubes, plasma from burn mice activated the same inflammatory and proteolytic pathways, leading to myotube atrophy. In mice with burn injury, the intraperitoneal injection of C188-9 (50 mg/kg) reduced activation of the STAT3 and ubiquitin-proteasome proteolytic pathways, reversed skeletal muscle atrophy, and increased grip strength. Similarly, pretreatment of murine C2C12 myotubes with C188-9 (10 µM) reduced activation of the same inflammatory and proteolytic pathways, and ameliorated myotube atrophy induced by plasma taken from burn model mice. Collectively, these results indicate that pharmacological inhibition of STAT3 signaling may be a novel therapeutic strategy for thermal burn-induced skeletal muscle wasting.